PENGARUH ABSENTEEISM DAN JOB ATTITUDE TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN LEASING DI KOTA PADANG - Lukito, Hendra; Utama, M Kurnia (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
This study aims to examine and analyze the effect of absenteeism and job attitude on employee performance in leasing companies in Padang City, West Sumatra Province. Absenteeism defined as the absenteeism of employees from their work responsibility. Job attitude can be measured through job satisfaction and organizational commitment. The population was all employees who work at one of the leasing companies located in Padang. The sampling method used was saturated sampling (census). Research data was collected by distributing questionnaires to a total of 43 respondents. Data processing and analysis were performed using a multiple linear regression method run by SPSS version 22.0. The results of the study indicated that absenteeism has no significant effect on employee performance. Job satisfaction, as part of job attitude, had a significant effect on employee performance, while organizational commitment did not significantly affect performance.